Prognostic Value of Tc99m-Pertechnetate Thyroid Scintigraphy in Radioiodine Therapy in a Cohort of Chinese Graves' Disease Patients: A Pilot Clinical Study. (24th March 2015) - Hou, Haifeng; Hu, Shu; Fan, Rong; Sun, Wen; Zhang, Xiaofei; Tian, Mei
Abstract : Objectives . This study is to assess the prognostic value of Tc 99m -pertechnetate thyroid scintigraphy for predicting the outcomes of fixed low dose of radioiodine therapy (RIT) in a cohort of Chinese Graves' disease (GD) patients. Materials and Methods . This is a retrospective study of GD patients who received RIT with a single dose of radioiodine (5 mCi). All the patients received Tc 99m -pertechnetate thyroid scintigraphy prior to RIT. Thyroid mass, Tc 99m -pertechnetate uptake, gender, age at diagnosis, duration of the disease, ophthalmopathy, and serum levels of FT4, FT3, TT4, and TT3 prior to RIT were analyzed as potential interference factors for outcomes of RIT. Results . One hundred and eighteen GD patients who completed RIT were followed up for 12 months. The outcomes (euthyroidism, hypothyroidism, and hyperthyroidism) were found to be significantly associated with thyroid mass and Tc 99m -pertechnetate uptake. Patients with thyroid mass ≤ 40.1 g or Tc 99m -pertechnetate uptake ≤ 15.2% had higher treatment success. Conclusions . A fixed low dose of 5 mCi radioiodine seems to be practical and effective for the treatment of Chinese GD patients with thyroid mass ≤ 40.1 g and Tc 99m -pertechnetate uptake ≤ 15.2%. This study demonstrates Tc 99m -pertechnetate thyroid scintigraphy is an important prognostic factor for predicting the outcomes of RIT.